Penentuan Densitas Akrilik Dan Plastik Berdasarkan Citra Radiografi Digital: Gede Arya Wiguna, Almahdi M Alshweikh, Gede B Suparta, Andreas C Louk, Kus Kusminarto - Gede A. Wiguna Gede A. Wiguna; Almahdi M. Alshweikh Almahdi M. Alshweikh; Gede B. Suparta Gede B. Suparta; Andreas C. Louk Andreas C. Louk; Kus Kusminarto Kus Kusminarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
X-ray radiography is an imaging technique that utilizes continuous X-ray radiation that penetrates objects. This technique is a non-destructive technique that is widely used for nondestructive testing in industry and for diagnostics in health. This paper is reported the use of digital micro x-ray radiography equipment which was made by the Physics Department of FMIPA UGM to measure the density of plastic and acrylic materials. For this reason, phantom step wedge is made from acrylic and plastic materials. Density is calculated based on variations in the intensity difference that passes through the step wage phantom. Based on the computation, the result obtained acrylic density value of 0.79 ± 0.01 g / cm3 and plastic density of 0.92 ± 0.01 g / cm3. If the computation of the density value is directly compared to the value of density computation using digital radiography, the digital radiography density value is approxaimetely lower 34.18% for acrylic material and 23.91% for plastic material.